Response to Terrorism - The Use of Force Against International Terrorism - Almizory, Arsalan H. (Academic Journal of Nawroz University, 2017)
The events of 11 September 2011 overwhelmingly challenged the existing principles of international law, both as the principles of international humanitarian law and as the right of state to use military force. This article assesses the uncertainty about the definition of terrorism, and how international law can provide legal framework by which to state responses to acts of terrorism, whether the acts are committed by organizations or by non-state actors. It scrutinizes the difficulties of applying the rules of international humanitarian law in selecting military objectives when directing attacks against terrorists and in classifying captured fighters. Eventually, it considers whether the right of self-defense extends to military responses to terrorists acts, since most such responses violate the territorial integrity of a state that is not itself directly responsible.